Would decentralisation have made a difference? - Pathak, vidyadhar; Patel, Shirish (2005)
Mumbai needs governance of a different kind, decentralised to a local level and run by individuals more clearly answerable for their local performance, rather than being run by ministers who have state-wide responsibilities and constituencies. This article describes current planning procedures, and looks at a Canadian alternative based on public participation, consensus building and a devolution of local planning to local authorities. It also suggests that the mayor-in-council system of governance, successfully pursued in Kolkata, might have produced a more effective response to the disaster. - Reproduced.
Keywords: Decentralization - India - Maharashtra; Decentralization